2010
DOI: 10.1111/j.1420-9101.2010.02148.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic structure of Borrelia afzelii varies with geographic but not ecological sampling scale

Abstract: The genetic structure of a pathogen is an important determinant of its potential rate of adaptation and can thereby influence the dynamics of host–parasite interactions. We investigated how the genetic structure of Borrelia afzelii varies with geographic and ecological sampling scale. Genetic structure was measured as the degree of linkage disequilibrium (LD) across three loci. To test for the effects of geographic and ecological scale, we calculated LD across or within populations 4–82 km apart and across or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 36 publications
5
63
0
Order By: Relevance
“…These species are the most common small mammals in the study area, and together make up approximately 90% of the small mammal community [13]. Animals were caught with live traps (Ugglan Special, GrahnAB, Sweden), baited with oat and apple.…”
Section: Materials and Methods (A) Small Mammal Sampling And Dna Extramentioning
confidence: 99%
See 4 more Smart Citations
“…These species are the most common small mammals in the study area, and together make up approximately 90% of the small mammal community [13]. Animals were caught with live traps (Ugglan Special, GrahnAB, Sweden), baited with oat and apple.…”
Section: Materials and Methods (A) Small Mammal Sampling And Dna Extramentioning
confidence: 99%
“…[19], applying the following temperature programme: 508 for 2 min, 958 for 2 min followed by 40 cycles of 958 for 30 s, 528 for 30 s and 728 for 45 s. Primers for amplification of a 340bp-long rrs-rrlA IGS fragment were designed with the software GENEIOUS (v. 5.0, Biomatters, Auckland, New Zealand) using previously described rrs-rrlA IGS sequences [13]. The forward primer IGS_F1 (P202) 5 0 -TCGTACTGGAAGTGTGGCT-3 0 was combined with the reverse primer IGS_R1 (P203) 5 0 -TTTGTCAATTTCGA TGTTAGRGT-3 0 and the cycling parameters were: 508 for 2 min, 958 for 2 min followed by 40 cycles of 958 for 30 s, 618 for 30 s and 728 for 45 s. These trials and an additional test using 454 fusion primers in standard PCR showed that 38 amplification cycles were optimal for accurate downstream detection and quantification of strains for both ospC and rrs-rrlA IGS targets.…”
Section: (B) Optimization Of Amplificationmentioning
confidence: 99%
See 3 more Smart Citations